The Gas Chromatography-Mass Spectrometry (GC-MS) Analysis of Seed Oil of Retama Raetam - Aisha Alwasia; Ahmed Alhamrouni; Omaro A. Aburas; Emhamed Boras; Asmahan Abukhdir; Salwa Muftah Eljamay (African Journal of Advanced Pure and Applied Sciences, 2023)
One of the most accurate techniques for identifying the various secondary metabolites present in plant oils is gas chromatography-mass spectrometry (GC-MS). The seed oil of Retama raetam was analyzed by GC-MS to detect various compounds present in it. The GC-MS analysis revealed 47 chemical compounds. (4-Bromophenyl) bis (2, 4-dibromophenyl) amine (54.78 min) is the highest retention time chemical compound, followed by 2, 7, 12, 17-tetrabrom (allàs) cyclotetrathiophen (5.17 min) as the lowest retention time chemical compound. The most abundant phytocompounds identified in seed oil of Retama raetam are 9,12-octadecadienoicacid (Z,Z), methyl ester (42.86%), dodecanoic acid, 3,7,11 trimethyl, methyl ester (19.42%), and 9-octadecenoic acid (Z,Z), methyl ester (13.77%), respectively. In vitro antimicrobial screening of the seed oil of Retama raetam against Gram-positive (St. aureus ATCC 25923) and Gram-negative (E. coli ATCC 25922) and Ps. aureginosa ATCC 25850) bacteria was evaluated in this study, and the obtained results revealed activity only against St. aureusas, with no activity recorded against E. coli or Ps. aureginosaas. Fungi (Candida albicans ATCC 10213) was also evaluated, with no activity recorded for different concentrations of the seed oil of Retama raetam (100%, 50%, and 25%). Thus, it indicates that the seed oil of Retama raetam has activity only against St. aureus. The resultant antibacterial activity exhibited by the seed oil of Retama raetam is related to the presence of phytocompounds identified in the seed oil of Retama raetam, which were identified by using GC-MS and reported to have antimicrobial and antibacterial activity.